2014
DOI: 10.1182/blood-2013-11-537217
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated cell death and lymphocyte homeostasis cause premature lethality in mice lacking the BH3-only proteins Bim and Bmf

Abstract: Key Points• BH3-only proteins Bim and Bmf jointly coregulate developmental cell death.• Bim and Bmf act as a barrier against autoimmunity and malignant disease.BH3 domain-only proteins (BH3-only) proteins are members of the Bcl-2 family that play crucial roles in embryogenesis and the maintenance of tissue homeostasis by triggering apoptotic cell death. The BH3-only protein Bim is critical for developmental apoptosis of lymphocytes, securing establishment of tolerance and for the termination of immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 35 publications
3
50
0
Order By: Relevance
“…The PCR protocols for genotyping of mouse mammary tumor virus (MMTV)-Cre transgenic (line A) and WAP-Cre transgenic mice [Tg(MMTV-cre)1Mam and Tg-(Wap-cre)11738Mam, respectively] as well as the CAG-LSL-green fluorescent protein (GFP) Cre/loxP reporter strain can be found elsewhere (27)(28)(29). The generation of conventional BMF-and BIM-knockout mice as well as BMF/BIM-double-knockout mice was described earlier (30)(31)(32). All animals used in this study were treated humanely and in accordance with institutional guidelines and federal regulations.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR protocols for genotyping of mouse mammary tumor virus (MMTV)-Cre transgenic (line A) and WAP-Cre transgenic mice [Tg(MMTV-cre)1Mam and Tg-(Wap-cre)11738Mam, respectively] as well as the CAG-LSL-green fluorescent protein (GFP) Cre/loxP reporter strain can be found elsewhere (27)(28)(29). The generation of conventional BMF-and BIM-knockout mice as well as BMF/BIM-double-knockout mice was described earlier (30)(31)(32). All animals used in this study were treated humanely and in accordance with institutional guidelines and federal regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Bmf −/− lymphocytes, such as pre-B cells, showed no or only minor resistance to apoptotic stimuli, but this resistance was massively increased on additional loss of even only one allele of Bim, exceeding resistance observed in Bim −/ − cells. 32 Given that Tregs require continuous TCR signalling for their maintenance and function, 33 it was surprising that we did not observe higher A1 protein levels in Tregs when compared with conventional T cells (Tcons). It has been reported that A1 mRNA levels are high in splenic Tregs but even higher in thymic Tregs when compared with the expression observed in CD4 + Tcons.…”
mentioning
confidence: 98%
“…Phenocopies Bim −/− mice regarding development; infertile males due to defective spermatogenesis (later than in Baxdeficient mice) Coultas et al 2005 Bim/Bmf Born at reduced frequency, similar to Bim −/− mice; webbed feet; increased incidence of vaginal atresia (65%) and malocclusion of the incisors (25%); increased resistance of Hubner et al 2010;Labi et al 2014;Woess et al 2015;Sakamoto et al 2016 Continued Tuzlak et al et al 2009). As a consequence, hepatocytes or pancreatic β cells from BID-deficient mice are insensitive to Fas ligation in vivo (Yin et al 1999).…”
mentioning
confidence: 98%